PENGARUH PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BATU (Studi Kasus Pada Dinas Pendapatan Kota Batu Tahun 2012 - 2016) - Zainul Fikri; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT The purpose of this research is: 1) to analyze the influence of the hotel tax on the Local Revenue, 2) to analyze the influence of the restaurant tax on the Local Revenue, 3) to analyze the influence of the entertainment tax on the Local Revenue The research object used in this study is the local revenue that derived from hotel taxes, restaurant taxes and entertainment taxes in 2012 – 2016. Based on the results of this study show that the hotel tax has a positive and significant influence on local revenue in 2012 – 2016, this can be shown by the significant of the hotel tax is 0,000 < 0,05. The analysis of this study indicates that restaurant taxes have an influence on local revenue. Restaurant tax has a positive and significant influence on local revenue in 2012 – 2016, this can be shown by the significant of the restaurant tax is 0,004 < 0,05. The analysis of this study indicates that restaurant taxes have an influence on local revenue. Entertainment tax has a positive and significant influence on local revenue in 2012 – 2016, this can be shown by the significant of the enterteinment tax is 0,000 < 0,05. The analysis of this study indicates that entertainment taxes have an influence on local revenue. Keyword : Hotel Tax, Restaurant Tax, Entertainment Tax, Local Revenue